BT10 : Tìm x biết:
1) 9 \(⋮\) 2x + 1
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{x+1+3}{x+1}=\frac{x+1}{x+1}+\frac{3}{x+1}\)
\(\Rightarrow x+1\in\text{Ư}\left(3\right)=\left\{1;-1;3;-3\right\}\)
\(\Rightarrow x\in\left\{0;-2;2;-4\right\}\)
Ta có :
\(x+1+3⋮x+1\)
=> \(x+1+3-\left(x+1\right)⋮x+1\)
=> \(3⋮x+1\)
=> \(x+1\inƯ_3\)
=> \(x+1\in\left\{1;3;-1;-3\right\}\)
=> \(x\in\left\{0;2;-2;-4\right\}\)
\(\frac{x+5}{x+1}=\frac{x+4+1}{x+1}=\frac{x+1}{x+1}+\frac{4}{x+1}\)
\(\Rightarrow x+1\in\text{Ư}\left(4\right)=\left\{1;2;4;-1;-2;-4\right\}\)
\(\Rightarrow x\in\left\{0;1;3;-2;-3;-5\right\}\)
x+5\(⋮\)x+1
x+1+4\(⋮\)x+1
Vì x+1\(⋮\)x+1
Buộc 4\(⋮\)x+1=>x+1ϵƯ(4)={1;2;4}
Với x+1=1=>x=0
x+1=2=>x=1
x+1=4=>x=3
Vậy xϵ{0;1;3}
Giải:
Ta có:
\(x+8⋮x+1\)
\(\Rightarrow\left(x+1\right)+7⋮x+1\)
\(\Rightarrow7⋮x+1\)
\(\Rightarrow x+1\in\left\{1;-1;7;-7\right\}\)
+) \(x+1=1\Rightarrow x=0\)
+) \(x+1=-1\Rightarrow x=-2\)
+) \(x+1=7\Rightarrow x=6\)
+) \(x+1=-7\Rightarrow x=-8\)
Vậy \(x\in\left\{0;-2;6;-8\right\}\)
\(\frac{x+8}{x+1}=\frac{x+7+1}{x+1}=\frac{x+1}{x+1}+\frac{7}{x+1}\)
\(\Rightarrow x+1\in\text{Ư}\left(7\right)=\left\{1;7;-1;-7\right\}\)
\(\Rightarrow x\in\left\{0;6;-2;-8\right\}\)
\(\frac{x+4}{x}=\frac{x}{x}+\frac{4}{x}\)
\(\Rightarrow x\in\text{Ư}\left(4\right)=\left\{1;2;4;-1;-2;-4\right\}\)
Ta có :
\(x+4⋮x\)
=> \(x+4-x⋮x\)
=> \(4⋮x\)
=> \(x\inƯ_4\)
=> x\(\in\left\{1;2;4;-1;-2;-4\right\}\)
a: =-1/5x^5y^2
b: =-9/7xy^3
c: =7/12xy^2z
d: =2x^4
e: =3/4x^5y
f: =11x^2y^5+x^6
`@` `\text {Ans}`
`\downarrow`
`a,`
`x^2 + 2x + 1 = 9`
`=> x^2 + 2x + 1 - 9 = 0`
`=> x^2 + 2x - 8 = 0`
`=> x^2 + 4x - 2x - 8 = 0`
`=> (x^2 + 4x) - (2x + 8) = 0`
`=> x(x + 4) - 2(x + 4) = 0`
`=> (x-2)(x+4) = 0`
`=>`\(\left[{}\begin{matrix}x-2=0\\x+4=0\end{matrix}\right.\)
`=>`\(\left[{}\begin{matrix}x=2\\x=4\end{matrix}\right.\)
Vậy, `x \in {2; 4}`
`b,`
`x^2 - 1 = 15`
`=> x^2 = 15 + 1`
`=> x^2 = 16`
`=> x^2 = (+-4)^2`
`=> x = +-4`
Vậy, `x \in {4; -4}`
`c)`
`19 - 2x^2 = 1`
`=> 2x^2 = 19 - 1`
`=> 2x^2 = 18`
`=> x^2 = 18 \div 2`
`=> x^2 = 9`
`=> x^2 = (+-3)^2`
`=> x = +-3`
Vậy, `x \in {3; -3}.`
`@` `\text {Ans}`
`\downarrow`
`a)`
`3x(4x-1) - 2x(6x-3) = 30`
`=> 12x^2 - 3x - 12x^2 + 6x = 30`
`=> 3x = 30`
`=> x = 30 \div 3`
`=> x=10`
Vậy, `x=10`
`b)`
`2x(3-2x) + 2x(2x-1) = 15`
`=> 6x- 4x^2 + 4x^2 - 2x = 15`
`=> 4x = 15`
`=> x = 15/4`
Vậy, `x=15/4`
`c)`
`(5x-2)(4x-1) + (10x+3)(2x-1) = 1`
`=> 5x(4x-1) - 2(4x-1) + 10x(2x-1) + 3(2x-1)=1`
`=> 20x^2-5x - 8x + 2 + 20x^2 - 10x +6x - 3 =1`
`=> 40x^2 -17x - 1 = 1`
`d)`
`(x+2)(x+2)-(x-3)(x+1)=9`
`=> x^2 + 2x + 2x + 4 - x^2 - x + 3x + 3=9`
`=> 6x + 7 =9`
`=> 6x = 2`
`=> x=2/6 =1/3`
Vậy, `x=1/3`
`e)`
`(4x+1)(6x-3) = 7 + (3x-2)(8x+9)`
`=> 24x^2 - 12x + 6x - 3 = 7 + (3x-2)(8x+9)`
`=> 24x^2 - 12x + 6x - 3 = 7 + 24x^2 +11x - 18`
`=> 24x^2 - 6x - 3 = 24x^2 + 18x -11`
`=> 24x^2 - 6x - 3 - 24x^2 + 18x + 11 = 0`
`=> 12x +8 = 0`
`=> 12x = -8`
`=> x= -8/12 = -2/3`
Vậy, `x=-2/3`
`g)`
`(10x+2)(4x- 1)- (8x -3)(5x+2) =14`
`=> 40x^2 - 10x + 8x - 2 - 40x^2 - 16x + 15x + 6 = 14`
`=> -3x + 4 =14`
`=> -3x = 10`
`=> x= - 10/3`
Vậy, `x=-10/3`
Ta có :
\(9⋮2x+1\)
=> \(2x+1\inƯ_9\)
=> \(2x+1\in\left\{1;3;9\right\}\)
=> \(2x\in\left\{0;2;8\right\}\)
=> \(x\in\left\{0;1;4\right\}\)
Vậy \(x\in\left\{0;1;4\right\}\)